Pengaruh Model Discovery Learning terhadap Pemahaman Konsep Siswa pada Materi Jamur: (The Effect of Discovery Learning Models on Students' Conceptual Understanding of Fungi) - Mustofa, Zainul; Indrati, Dika Agustia (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
Based on the observation results, it was found that students' understanding of the concept of fungi was still low. This study examines how the Discovery Learning Model affects the understanding of 10th grade students at SMA Negeri 5 Tuban. The quantitative approach was conducted using a pre-experimental method and one group pre-test post-test design. This study involved 34 students from class X-B who were selected through purposive sampling. N-Gain score computations, normality tests, and hypothesis testing with paired sample t-tests were all part of the data analysis. The research findings show an increase in the mean value of 40.62. The paired sample t-test shows a significance value of 0.000 at a significance level of 5%, indicating a significant effect before and after the application of the learning model. The N-Gain test results reinforce these findings with a mean value of 74.57% in the fairly effective category. Thus, the Discovery learning model has been proven effective as an alternative learning model for improving students' ability to understand biological concepts, especially those related to fungi. Abstrak. Pemahaman konsep siswa tentang biologi, terutama yang berkaitan dengan jamur masih kurang. Penelitian ini mengkaji bagaimana Model Pembelajaran berbasis Penemuan ( Discovery Learning ) mempengaruhi pemahaman siswa kelas X SMA Negeri 5 Tuban. Pendekatan kuantitatif dilakukan menggunakan metode pra-eksperimen dan desain one group pre-test and post-tes . Penelitian ini melibatkan 34 siswa dari kelas XB yang dipilih melalui purposif sampling . Perhitungan skor N-Gain, uji normalitas, dan uji hipotesis dengan uji t sampel berpasangan merupakan bagian dari analisis data.Temuan penelitian menunjukkan adanya kenaikan nilai mean sebesar 40,62. Uji peered sample t-test menunjukkan nilai signifikansi sebesar 0,000 pada taraf signifikansi 5%, yang mengindikasikan adanya efek signifikan sebelum dan setelah penerapan model pembelajaran. Hasil uji N-Gain memperkuat temuan tersebut dengan nilai mean 74,57% dalam kategori cukup efektif. Jadi, model pembelajaran Discovery telah terbukti efektif sebagai model pembelajaran alternatif untuk meningkatkan kemampuan siswa dalam memahami konsep biologi, terutama terkait jamur.